Hubungan Karakteristik Pasien Hipertensi Dengan Kepatuhan Minum Obat di UPT Puskesmas Meral Kabupaten Karimun Tahun 2020 - Delladari Mayefis; Suhaera; Yuni Sartika Sari (Yayasan Literasi Sains Indonesia, 2022)
Hypertension is a condition when blood pressure is high. High blood pressure is the force exerted by circulating blood to the arterial walls of the body, the main vessels in the body. The research objective was to see the relationship between hypertensive patients and taking medication at the Meral Public Health Center, Karimun Regency. The method used is research in the form of an analytical survey, which is research that finds out how health phenomena occur by analyzing the dynamics of the phenomenon or between risk factors and effect factors. The results of the study, namely the chi square statistical test obtained p value = 1,000, which means that the p value is greater than 0.05 (1,000> 0.05), this indicates that there is a relationship between the age group of the respondents and taking anti-hypertensive drugs. The results of the chi square statistical test obtained p value = 0.015, which means that the p value is smaller than 0.05 (0.000 <0.05), this indicates that there is a relationship between the respondent's education level and taking anti-hypertensive drugs. The conclusion from this research on the relationship between nation and taking medicine is the age and education level of the respondents.